Improved Compression Efficiency in H.264/AVC using intra prediction modes for Information Hiding - Saurabh Anand (International Journal of Advanced Science and Technology, 2020)
Video compression is generally referred to minimizing the capacity of data which can be used to display video images effectively without affecting the perceptual quality. As it takes up so much of space, video needs to be compressed prior to being put on the network i.e. web. “Compressed” just signifies that the information is put up into a smaller space. In general, there are two basic types of compression - lossy and lossless. By producing small files in comparison with the original one, lossy compression compensates for the quality degradation. Lossless compression is what it exactly sounds similar to, a technique of compression where there is no loss of the information. This is a kind of technique which is not that useful as files frequently finish up of being the similar size as before compression they were. It may point useless, as the primary goal of compression of ours is reducing the file size. However, if file size reduction is not a matter of concern, then using lossless compression is a better option as this will lead to a perfect-quality picture. Keywords: Compression, Lossy, Lossless